FAKTOR YANG MEMPENGARUHI IMPLEMENTASI SAK ETAP PADA UMKM DENGAN KETIDAKPASTIAN LINGKUNGAN SEBAGAI VARIABEL MODERASI - Indah Anisykurlillah; Bergas Rezqika (Jurnal Riset Keuangan dan Akuntansi, 2019)
This research aims to determine the effect of educational background, business size, business age, understanding of technology, socialization and training on the Implementation of SAK ETAP and its effects when moderated by environmental uncertainty. The study population was oyster mushroom MSMEs that were spread in Temanggung Regency, a total of 48 MSMEs. Sampling using saturation sampling technique, then obtained a sample of 48 respondents for analysis. The data analysis technique used is the Moderate Regression Analysis (MRA) with the help of IBM SPSS Statistics 21 program. The results showed that socialization and training had a significant positive effect on the implementation of SAK ETAP. Environmental uncertainty strengthens the relationship of socialization and training to the implementation of SAK ETAP. Educational background, business size, and understanding of technology have no effect on the implementation of SAK ETAP. Environmental uncertainty cannot moderate the relationship of educational background and implementation of SAK ETAP. Environmental uncertainty cannot moderate the relationship between understanding technology and implementing SAK ETAP. The conclusions of this research indicate that the higher the frequency of socialization and training has an effect on the implementation of SAK ETAP and environmental uncertainty can be used as moderation because it is able to strengthen business size, business age and socialization and training. Keywords: Implementation of SAK ETAP; Educational Background; Business Size; Business Age; Understanding of Technology; Socialization and Training; Environmental Uncertainty